Outcome of Anderson Hynes Dismembered Pyeloplasty in Paediatric Pelvic Ureteric Junction Obstruction - Sah, Priyanka; Adhikari`, Suman Bikram; Basnet, Bal Mukund; Yadav, Kajal kumari Singh; Rupakhet, Amar Nath; Shah, Mahesh Kumar (Grande Medical Journal, 2025)
BackgroundAnderson Hynes dismembered pyeloplasty is the gold standard procedure for management of Pelvic Ureteric Junction Obstruction (PUJO) in children with success rate of 90-95%. The aim of the current study is to evaluate safety, efficacy and outcomes of Anderson Hynes Pyeloplasty in our part of the world.MethodA retrospective study was conducted involving 69 children who underwent Open Anderson Hyne’S dismembered Pyeoplasty over a period of 2 years from March 2022 to April 2024. Patient were evaluated with respect to age, sex, ultrasonographic grading of hydronephrosis, affected side, operation time, postoperative complications and follow-up outcomes and analyzed.ResultThis study consisted of 69 patients with moderate to severe hydronpehrosis secondary to PUJO underwent open pyeloplasty. Male-female ratio was 2:1. Average mean age was 41.67 months (1 month to 156 months) where 28 patients (40.57%) were infants. 45 patients (65.2%) had grade 3 hydronephrosis whereas 24 patients (34.8%) had grade 4 hydronephrosis in ultrasound abdomen. Right sided pyeloplasty was performed in 48 children (69.6%) and left sided was performed in 21 children (30.4%). Mean operative time period was 92.5 minutes with mean hospital stay of 3.53 days (3 days to 5 days). Post-pyeloplasty, 63 patients (91.3%) showed improvement in ipsilateral kidney function on DTPA scan and three patient developed anastomotic stricture which required Re-do Pyeloplasty.ConclusionAnderson Hyne’s dismembered pyeloplasty has shown better outcome amongst pediatric patient with PUJO. It has a high success rate with significant improvement in kidney drainage function.